1984
DOI: 10.1109/jqe.1984.1072386
|View full text |Cite
|
Sign up to set email alerts
|

The slab geometry laser - Part I: Theory

Abstract: Abstract-Slab geometry solid-state lasersoffer significant performance improvements over conventional rod geometry lasers. We present a detailed theoretical description of the thermal, stress, and beam propagation characteristics of a slab laser. Our analysis includes consideration of the effects of the zig-zag optical path which eliminates thermal and stress focusing and reduces residual birefringence. S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(124 citation statements)
references
References 11 publications
3
121
0
Order By: Relevance
“…[4] is necessary for determining the radially varying index of refraction d d n T , and the calculate stresses. By using Equations (1)- (3), Abouricha et al [4] demonstrated that the temperature expressions of the stress components can be written as: [1] [8] ( ) ( ) ( ) ( )…”
Section: Theoretical Modelmentioning
confidence: 99%
“…[4] is necessary for determining the radially varying index of refraction d d n T , and the calculate stresses. By using Equations (1)- (3), Abouricha et al [4] demonstrated that the temperature expressions of the stress components can be written as: [1] [8] ( ) ( ) ( ) ( )…”
Section: Theoretical Modelmentioning
confidence: 99%
“…How to remove the waste heat and reduce the thermal effects efficiently usually are main considerations in the design of high average power systems. In related articles [20], consequences of thermal and thermomechanical effects have been discussed for slab lasers and amplifiers. The analyses of nonlinear thermal effects in slab lasers are also presented in ref.…”
Section: High-power Nd:yag Planar Waveguide Lasersmentioning
confidence: 99%
“…Forced gas or low dielectric constant liquid cooling of the crystal in the cavity could be considered. Techniques of correcting thermal lensing utilized by optical slab amplifier designers may also be applicable in some modified form [7].…”
Section: Rf Waveformmentioning
confidence: 99%